Geopolitics : the geography of international relations - Cohen, Saul Bernard (Rowman & Allanheld, 2015)
Written by one of the world's leading political geographers, this fully revised and updated textbook examines the dramatic changes wrought by ideological, economic, sociocultural, and demographic changes unleashed since the end of the Cold War. Saul Cohen considers these forces in the context of their human and physical settings and explores their geographical influence on foreign policy and international relations